COOPERATIVE LEARNING DENGAN MODEL TGT (TEAMS GAMES TOURNAMENT) MATERI BILANGAN BULAT BAGI SISWA KELAS IV SEKOLAH DASAR - Endrayana Putut L.E. (Universitas PGRI Adi Buana Surabaya, 2017)
Mathematics is a science that underlies the development of modern technology, has an important role in various disciplines and advance the human mind. The development in the field of information and communication technology is influenced and based on the development of Mathematics. Mathematics is a lesson that is directly related to the development of science and technology, both material and its usefulness. So Mathematics needs to be developed and upgraded including materials, teaching and learning process, environment as well as school facilities, as the special purpose of teaching Mathematics in primary school is to develop numeracy skills that are useful in everyday life. Based on the results of observations during the learning, the problem faced by students is the lack of mastery of the concept of integers so that student learning outcomes are still lacking. Teachers also still dominate learning by lecturing method so that happened is teacher centered. This makes the learners less motivated and less enthusiastic in following the lesson. For that we need to make changes in learning that is with the model of learning that creates learning to be student centered. So learning activities centered on the learners, teachers as a motivator and facilitator in it so that the atmosphere of the classroom more conducive. Teams Games Tournament (TGT) becomes one of the learning models that can be applied to change the above paradigm. This is evident in significant changes in post test results of students versus pre test results. Keywords: Teams Games Tournament (TGT), cooperative, students centered